Design of Hybrid Learning in Classroom Using Web Camera and Website - Basuki Putra, Ghiri; Arkan, Fardhan; Asmar; Taqiyuddin (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2024)
The Covid pandemic that hit the world including Indonesia caused changes in lifestyle and ways of working and studying to prevent the transmission of COVID-19 virus. This is certainly a challenge for education in the era of the pandemic on how the learning process can be proceeded so the knowledge is conveyed. Hybrid learning is a combination of some learning methods; online method (outside classroom) with face-to-face meeting method for several hours (inside classroom). Therefore, hybrid learning is suitable to be carried out during this pandemic. Hybrid learning is built in a class that is built based on Internet and uses web camera technology that can be done anywhere with the Internet by students and lecturers. This class provides hybrid learning process using website and 4G internet network so that students get a better learning experience and understanding easier to learn materials. The web camera is utilized as a student online learning process that views the movement of the lecturer so that it makes learning easier for the student. This hybrid learning also uses website to support in-class monitoring and future hybrid learning processes and capable of recording the learning process so the recording can be used in the future.